2000
DOI: 10.1111/j.1528-1157.2000.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Mapping of Genes for Epilepsy in NER: A Rat Strain with Tonic‐Clonic Seizures

Abstract: Summary:Purpose: NER is a mutant rat strain that exhibits spontancous tonic-clonic convulsions accompanied by epileptic discharges on ictal EEG and serves a s a model for generalized tonic-chic seizures in humans. Our previous experiments have suggested that a major autosomal rccessive gene and several minor genes regulate the inheritance of tonic-chic seizures in NER. The purpose of this study was to confirm the mode of inheritance and to locate the causative genes for epilepsy in NER on the rat genetic map.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Genes that influence a mutant phenotype can be identified systematically by evaluating the seizure phenotype on different background strains. Several strain‐dependent seizure susceptibility loci and genes have been identified (Chaix et al 2007; Ferraro et al 2001, 2004, 2007a,b, 2010, 2011; Frankel et al 1995; Gershenfeld et al 1999; Legare et al 2000; Maihara et al 2000; Winawer et al 2011).…”
mentioning
confidence: 99%
“…Genes that influence a mutant phenotype can be identified systematically by evaluating the seizure phenotype on different background strains. Several strain‐dependent seizure susceptibility loci and genes have been identified (Chaix et al 2007; Ferraro et al 2001, 2004, 2007a,b, 2010, 2011; Frankel et al 1995; Gershenfeld et al 1999; Legare et al 2000; Maihara et al 2000; Winawer et al 2011).…”
mentioning
confidence: 99%
“…The seizures are inhibited by conventional antiepileptics such as diazepam, valproate, phenobarbital, and carbamazepine, but rarely inhibited by phenytoin, zonisamide, and ethosuximide (12). The genes responsible for the seizures of NER, designated Ner1 and Ner2, were found to be located on chromosomes 1 and 3, respectively (13). In addition to these findings, we have recently found that hippocampal CA3 neurons of young NER show a long-lasting depolarization shift accompanied by repetitive firings following a single stimulation of the mossy fibers, before spontaneous seizures appear manifestly (8).…”
Section: Discussionmentioning
confidence: 77%
“…Since the initial efforts on diabetes, QTL have been located for a wide variety of phenotypes (Rikke and Johnson 1998), including atherosclerosis (Hyman et al 1994;Ko et al 2001;Mu et al 1999;Paigen et al 1987a,b;Pitman et al 1998;Purcell et al 2001); epilepsy (Frankel et al 1995a,b;Gershenfeld et al 1999;Legare et al 2000;Maihara et al 2000;Miner and Marley 1995); obesity (Brockmann et al 2000;Horvat et al 2000;Schalling et al 1999;Taylor et al 1999Taylor et al , 2001; asthma (De Sanctis and Drazen 1997;De Sanctis et al 1999;Dwyer-Nield et al 2000;Ewart et al 2000;Nicolaides et al 1997;Symula et al 1999); lupus (Gu et al 1998;Santiago et al 1998); osteoporosis (Benes et al 2000;Hosoi 2001;Shimizu et al 1999); hypertension (Sugiyama et al 2001a,b); and a variety of cancers including lung (Festing et al 1994Lin et al 1998), skin (Nagase et al 1996(Nagase et al , 1999(Nagase et al , 2001, and colon (Gould and Dove 1998;MacPhee et al 1995).…”
Section: Natural Polymorphismsmentioning
confidence: 98%